2008
DOI: 10.1111/j.1745-4565.2008.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR METHOD FOR THE DETECTION OF GENUS FUSARIUM AND FUMONISIN‐PRODUCING ISOLATES FROM FRESHLY HARVESTED SORGHUM GRAINS GROWN IN KARNATAKA, INDIA

Abstract: Sixty‐four isolates of Fusarium species isolated from 44 sorghum samples collected during 2004–2005 were subjected to polymerase chain reaction (PCR) analysis. PCR detection was performed on all Fusarium species using two different sets of primers, namely, internal transcribed spacer (ITS) and FUM1. The developed protocol is rapid for small‐scale extraction of DNA from fungal mycelia for the detection of Fusarium species using diagnostic PCR. Sixty‐four Fusarium isolates, namely, Fusarium verticillioides (45),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…In this study, only three potential fumonisin producers could be identified. This result is surprising, as it is in contradiction with the data of Sreenivasa et al (2008) and Yazeed et al (2011), in which 53 of 64 plant-derived isolates and all of the 21 feed-samples-derived isolates, respectively, were identified as fumonisin producers. The results of the biological test are similar to the ones obtained by Bis (2006) in the analysis of potentially toxicogenic fungal strains isolated from soils in Cracow and its surroundings, where only 60% of the isolated strains could have been considered as toxic.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In this study, only three potential fumonisin producers could be identified. This result is surprising, as it is in contradiction with the data of Sreenivasa et al (2008) and Yazeed et al (2011), in which 53 of 64 plant-derived isolates and all of the 21 feed-samples-derived isolates, respectively, were identified as fumonisin producers. The results of the biological test are similar to the ones obtained by Bis (2006) in the analysis of potentially toxicogenic fungal strains isolated from soils in Cracow and its surroundings, where only 60% of the isolated strains could have been considered as toxic.…”
Section: Discussioncontrasting
confidence: 56%
“…isolates was analyzed in accordance with the PCR-based approach with FUM1-F and FUM1-R primer pair introduced by Sreenivasa et al (2008). In this study, only three potential fumonisin producers could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…All Fusarium isolates were identified up to species level based on the micro-morphological features, using fungal keys (Leslie & Summerell 2006). The identity was confirmed by PCR, using Fusarium genus specific primer sequences (Sreenivasa et al 2008).…”
Section: Fusarium Speciesmentioning
confidence: 99%
“…Previous workers (Baird et al, 2008 andSrinivasa et al, 2008) used this primer only with maize infecting Fusarium tissues. This study is the first effort on rice in Egypt represented banding size for both VERTF and Fum 5 primers.…”
Section: Dna Studiesmentioning
confidence: 99%